(untitled) (Sains Humanika, 2012)
This study was undertaken to determine the readiness of vocational school teachers in implementing School Enterprise Programme in technical schools in terms of knowledge content in enterprise module, entrepreneurship skills, attitude and the relationship between entrepreneurship skill with teachers’ attitude. By using a stratified sampling technique, a total of 236 teachers were selected from 15 vocational and technical schools in the South Zone which involves population of 586 teachers. Questionnaires were used as data resources and distributed to 236 teachers who are directly involved in the School Enterprise Programme. In general, the results of the survey showed the rspondents have sound knowledge of the entrepreneurship module. However, sound knowledge does not guarantee teachers are able to implement enterprising skills as many respondents are moderately equipped with the aforementioned skills. Attitude wise, many teachers have a satisfactory level regarding the implementation of The School Enterprise Programme where the highest mean value was belief element (mean=3.67), followed by initiative (mean=3.49) and interest (mean-3.34). While there are significant relationships between entrepreneurial skills with the attitude of school teachers in implementing Enterprise Program On the whole, the result shows that there is a need for greater exposure and the above aspect needs to be improved among vocational subject teachers.